Функциональные характеристики историзмов в исторических романах Вальтера Скотта - Коваленко, О. В.; Kovalenko, O. V. (Волинський національний університет імені Лесі Українки, 2012)
У статті зроблено спробу провести дослідження типів історизмів, які розглядаються як історичні реалії в історичних романах В. Скотта. Розглянуто функціональні характеристики історизмів, проаналізовано їхні функціональні типи. Досліджено схожості та різниці у функціонуванні різних типів історизмів в історичних романах В. Скотта. The article presents an attempt to investigate the functioning of historical words viewed as historical realia in W. Scott’s historical novels. Similarities and differences of different groups of historical words are subject to analysis. The functional types of historical words are indicated in the article.
Functional Сharacteristics of Historical Words in Walter Scott’s novels
Keywords: історичний роман; historical novel; історизм; historical word